Pembinaan Kegiatan Ekstrakurikuler di Sekolah Menengah Pertama Negeri Kota Sawahlunto - Fadhlyda, Richa; Erlamsyah, Erlamsyah; Daharnis, Daharnis (Universitas Negeri Padang, 2014)
Extracurricular activities in the Junior High School is one of self-development activities that require good coaching in the areas of planning, implementation and evaluation, but in reality it is less accomplished coaching. The population of this research is all the teacher coaches of extracurricular activities in junior high school Sawahlunto with a sample of 65 people. The results of the study coaching extracurricular activities in junior high school Sawahlunto already performing quite well in the areas of planning, implementation and evaluation f extra-curricular activities.